ANALISIS BIAYA PEMELIHARAAN AKTIVA TETAP DAMPAKNYA TERHADAP PENDAPATAN PADA PT. KAI (PERSERO) BANDUNG - Lia Yulianti; Hendra Abu Bakar (JURISMA : Jurnal Riset Bisnis & Manajemen, 2014)
PT.Â  KAI (Persero) is a company engaged in the field of document delivery services and other service activities. The method used in this research is descriptive method and quantitative approaches. The sample in this study is to report the income at PT.Â  KAI (Persero) from 2000 to 2007 for eight years and the statistical test used is the Simple Linear Regression Analysis, Correlation coefficients (Pearson product moment) and the coefficient of determination. Testing this hypothesis using the t test statistics of the parties with Î± = 0.05. Obtaining the results of the analysis processed by using SPSS version 15.0 for Windows. Based on the 0.951 correlation analysis showed a very strong relationship and the direction (positive) between the maintenance cost of fixed assets and income. Increased maintenance costs of fixed assets, followed by revenue increases. The coefficient of determination amounted to 90.44% indicating the existence of fixed asset maintenance cost analysis of the impact on earnings and the remaining 90.44% 9.56% influenced by other factors such as investment, economic conditions, and other costs.